Anti-yellowing polyurethane acrylate UV curing coating and preparation method thereof

By using composite chopped fibers and antioxidants in UV cured coatings, combined with the combination of nano zinc oxide and lignin, the problem of the paint turning yellow under long-term ultraviolet light irradiation is solved, and the yellowing resistance and adhesion are significantly improved.

CN119775883AActive Publication Date: 2025-04-08DONGZHOU CHEM IND (KUNSHAN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411820360.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-08
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

Existing UV curing coatings tend to turn yellow under long-term ultraviolet light, resulting in insufficient yellowing resistance and cannot meet the needs of varnish, white paint and outdoor decoration.

Method used

By introducing composite chopped fibers and antioxidants into UV cured coatings, fiber composite materials with a leather core structure are used, and the ultraviolet absorption effect of the coating is improved.

Benefits of technology

It significantly improves the yellowing resistance and adhesion of the coating, enhances the absorption and reflection ability of ultraviolet rays, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an anti-yellowing polyurethane acrylate UV (ultraviolet) curing coating. The anti-yellowing polyurethane acrylate UV curing coating is prepared from the following components in parts by weight: 60 to 70 parts of waterborne polyurethane acrylate, 5 to 10 parts of composite chopped fiber, 0.8 to 2.5 parts of antioxidant, 0.8 to 2.5 parts of flatting agent, 0.4 to 1.2 parts of dispersing agent, 1.5 to 3.5 parts of UV photoinitiator, 2 to 4 parts of matt powder, 5 to 10 parts of coalescing agent and 90 to 130 parts of water. Through reasonable formula design and introduction of an anti-ultraviolet absorption material, the waterborne polyurethane acrylate UV curing coating with yellowing resistance and good adhesive force is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of UV curing coatings, and in particular to an anti-yellowing polyurethane acrylate UV curing coating and a preparation method thereof. Background Art

[0002] Ultraviolet (UV) curing coatings are coatings that can undergo physical or chemical changes in a short period of time after being exposed to ultraviolet light or electron beams. In the past three decades, as people's environmental awareness has gradually increased, UV curing resins have been widely used due to their characteristics of being free of volatile solvents, low pollution, low energy consumption, fast curing, and excellent coating film properties. With the development and maturity of UV curing technology, unsaturated polyesters, photocurable inks, epoxy acrylates, and polyurethane acrylates (PUA) have been developed. The molecular structure of polyurethane acrylates contains both acrylate and carbamate functional groups. The paint film has good physical properties such as toughness, hardness, and strength, excellent adhesion, and relatively ideal comprehensive performance. PUA has the following excellent properties: (1) Heat resistance: The heat deformation temperature of most polyurethane acrylates is between 50 and 60°C; (2) Good mechanical properties: Polyurethane acrylate resins have the advantages of high elasticity, bending, deflection, and elongation; (3) Chemical resistance: Polyurethane acrylates have good resistance to dilute acids, dilute alkalis, and water, and excellent resistance to organic solvents. After long-term exposure to ultraviolet light, most coating surfaces have a tendency to change color and their mechanical properties deteriorate. Even indoors, they will be damaged by diffuse scattering or fluorescent radiation, resulting in yellowing or aging degradation. The main reason for coating aging is that the unsaturated bonds and benzene rings in the coating are susceptible to UV irradiation, reacting with oxygen to form peroxides and phthalic structures, which in turn affect the yellowing resistance of the coating. Since TDI is much cheaper than IPDI, most PUA water-based coatings on the market currently use TDI as a raw material. This type of coating turns yellow very seriously under light and cannot meet the needs of varnish, white paint and outdoor decoration. In terms of paint for home decoration, people prefer to use varnish, white paint and light-colored paint, and excellent yellowing resistance has become a requirement for the performance of high-end coatings. Summary of the invention

[0003] Technical problem to be solved: The purpose of the present invention is to provide a yellowing-resistant polyurethane acrylate UV-curing coating, and to prepare a yellowing-resistant and highly adhesive water-based polyurethane acrylate UV-curing coating through reasonable formula design and the introduction of anti-ultraviolet absorption materials.

[0004] Technical solution: An anti-yellowing polyurethane acrylate UV curing coating, comprising the following components in parts by weight: 60-70 parts of waterborne polyurethane acrylate, 5-10 parts of composite chopped fibers, 0.8-2.5 parts of antioxidant, 0.8-2.5 parts of leveling agent, 0.4-1.2 parts of dispersant, 1.5-3.5 parts of UV photoinitiator, 2-4 parts of matte powder, 5-10 parts of film-forming aid, 90-130 parts of water; Wherein, the antioxidant is any one or more of phosphite, antioxidant 1010 or antioxidant 168; The leveling agent is any one or more of polydimethylsiloxane, polydimethylphenylsiloxane or polyether modified polydimethylsiloxane; The dispersant is any one or more of dispersant BYK190, dispersant BYK167, dispersant BYK2050 or dispersant BYK-W966; The film-forming aid is a medium film-forming aid including any one or more of dipropylene glycol methyl ether, dipropylene glycol butyl ether, alcohol ester dodecahydrate, and diethylene glycol butyl ether; The photoinitiator is any one or more of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide. Preferably, the composite chopped fibers are a mixture of triangular cross-section fibers and circular cross-section fibers, the lengths of the triangular cross-section fibers and the circular cross-section fibers are 1-5 mm, and the mass ratio of the triangular cross-section fibers to the circular cross-section fibers is 10:3-8. Preferably, the method for preparing the composite chopped fibers comprises the following steps: S1. The flaky zinc oxide coated with lignin and nano-calcium carbonate were mixed and dispersed in a DMF solution, and a dispersant was added and ultrasonically dispersed for 30-60 min to obtain a mixed dispersion; S2. Dissolve polyacrylonitrile in DMF at a mass fraction of 10-15%, add the mixed dispersion at a volume ratio of 1:1, stir evenly and then vacuum degas to obtain a polyacrylonitrile cortex spinning solution; S3. The ultraviolet light absorber is added to the DMF solution and dispersed uniformly by ultrasonication to obtain an ultraviolet light absorber solution; S4. Dissolve polyacrylonitrile in DMF at a mass fraction of 10-15%, add a UV absorber solution, stir evenly, and then vacuum degas to obtain a polyacrylonitrile core spinning solution; S5. Selecting circular and triangular cross-section spinnerets respectively, coaxially spinning the spinning solutions prepared in steps S2 and S4 to obtain circular cross-section fibers and triangular cross-section fibers; S6. The two fibers prepared in step S5 are immersed in an inorganic acid solution to remove the nano-calcium carbonate in the cortex to obtain a porous surface fiber; S7. The fibers with porous surfaces are chopped into short pieces respectively, and the mixture is mixed according to a mass ratio to obtain composite chopped fibers. Preferably, the method for preparing the flaky zinc oxide coated with lignin comprises the following steps: S11. Add zinc nitrate hexahydrate to an ethanol aqueous solution, stir until dissolved, add urea, the molar ratio of zinc nitrate hexahydrate to urea is 1:1.5-2, stir and mix well, react at 180-190°C for 15-24h to obtain a precipitate, dry the precipitate and calcine at 500-550°C for 3-5h to obtain flaky nano zinc oxide; S12. The flaky nano zinc oxide prepared in step S11 is added to water and uniformly dispersed by ultrasonication to obtain a zinc oxide suspension; S13. Adding lignin to an alkaline aqueous solution and stirring until completely dissolved to obtain a lignin solution; S14. Add the lignin solution dropwise to the zinc oxide suspension and heat to react. The mass ratio of lignin to nano-flaky zinc oxide is 1-2:10. After the addition is complete, adjust the pH value of the solution to neutral and filter to obtain flaky zinc oxide coated with lignin. Preferably, in step S1, the mass ratio of the flaky zinc oxide coating the lignin to calcium carbonate is 2-4:1, and the concentration of calcium carbonate in DMF is 1-3wt%. Preferably, the content of the ultraviolet absorber in the polyacrylonitrile core layer spinning solution in step S4 is 0.1-0.4wt% Preferably, the inorganic acid in step S6 is any one of nitric acid, hydrochloric acid or sulfuric acid. The preparation method of the above-mentioned anti-yellowing polyurethane acrylate UV curing coating comprises the following steps: firstly, the water-based polyurethane acrylate is added into a container, and then composite chopped fibers, antioxidants, leveling agents, dispersants, UV photoinitiators, matte powders, film-forming aids and water are added in sequence, and each time a reaction raw material is added, the next raw material is added after being stirred evenly, and the anti-yellowing polyurethane acrylate UV curing coating is obtained after all the raw materials are added and mixed and stirred evenly. Beneficial effects: The anti-yellowing polyurethane acrylate UV curing coating of the present invention has the following advantages: 1. The present invention adds composite chopped fibers to the UV curing coating. The composite chopped fibers are composited with two fibers with different cross-sectional structures, one of which has a circular cross-sectional structure and the other has a triangular cross-sectional structure. The surface area of ​​the triangular cross-sectional fiber is larger than that of the ordinary circular cross-sectional fiber, and the fiber has a higher ultraviolet reflectivity. At the same time, the triangular cross-sectional fiber can form more reflection surfaces on the fiber surface, thereby reducing the transmittance of ultraviolet rays, and by changing the propagation path of light, the number of reflections of ultraviolet rays inside the fiber is increased, thereby improving the absorption efficiency of ultraviolet rays; 2. The composite chopped fibers of the present invention have a skin-core structure, an organic anti-ultraviolet agent is added to the core layer, and an inorganic composite anti-ultraviolet agent is added to the skin layer. When the coating is irradiated with ultraviolet light, the composite chopped fibers first reflect part of the ultraviolet light through the surface, and then the nano-sheet zinc oxide coated with lignin in the skin layer absorbs and reflects part of the ultraviolet light. Part of the ultraviolet light enters the interior of the fiber, and the organic anti-ultraviolet agent contained in the core layer absorbs the remaining ultraviolet light. The combination from the inside to the outside achieves a better ultraviolet absorption effect, thereby improving the yellowing resistance of the coating; 3. In the present invention, the ultraviolet absorption effect of the coating is further improved by combining nano zinc oxide and lignin. The composite short-cut fibers with appropriate content and length also have a certain influence on the final yellowing resistance and flexibility. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 The preparation method of the anti-yellowing polyurethane acrylate UV curing coating comprises the following steps: Weigh the following ingredients by weight: 60 parts of waterborne polyurethane acrylate, 5 parts of composite chopped fibers, 0.8 parts of phosphite, 0.8 parts of polydimethylsiloxane, 0.4 parts of dispersant BYK167, 1.5 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2 parts of matte powder, 5 parts of dipropylene glycol methyl ether, and 90 parts of water; Add waterborne polyurethane acrylate into a container, and then add composite chopped fibers, phosphite, polydimethylsiloxane, dispersant BYK167, 2-hydroxy-2-methyl-1-phenyl-1-propanone, matte powder, dipropylene glycol methyl ether and water in sequence, and after each reaction raw material is added and stirred evenly, add the next raw material until all the raw materials are added and mixed and stirred evenly to obtain an anti-yellowing polyurethane acrylate UV curing coating; The method for preparing composite chopped fibers comprises the following steps: S1. After mixing the flaky zinc oxide coated with lignin and nano-calcium carbonate, the mass ratio of the flaky zinc oxide coated with lignin and calcium carbonate is 2:1, dispersed in a DMF solution, and a dispersant is added, and ultrasonic dispersion is performed for 30 minutes to obtain a mixed dispersion, and the concentration of calcium carbonate in DMF is 1wt%; S2. Dissolve polyacrylonitrile in DMF at a mass fraction of 10%, add the mixed dispersion at a volume ratio of 1:1, stir evenly and then vacuum degas to obtain a polyacrylonitrile skin spinning solution; S3. The ultraviolet light absorber is added to the DMF solution and dispersed uniformly by ultrasonication to obtain an ultraviolet light absorber solution; S4. The polyacrylonitrile was dissolved in DMF at a mass fraction of 10%, and a UV absorber solution was added, and the mixture was stirred evenly and vacuum degassed to obtain a polyacrylonitrile core spinning solution having a concentration of 7 wt %, wherein the content of the UV absorber in the polyacrylonitrile core spinning solution was 0.1 wt %; S5. Selecting circular and triangular cross-section spinnerets respectively, coaxially spinning the spinning solutions prepared in steps S2 and S4 to obtain circular cross-section fibers and triangular cross-section fibers; S6. The two fibers prepared in step S5 are immersed in a 0.1 mol / L hydrochloric acid solution to remove the nano-calcium carbonate in the cortex to obtain a porous surface fiber; S7. The porous fibers were chopped into 1-5 mm and mixed in a mass ratio of 10:3 to obtain composite chopped fibers; The preparation method of the flaky zinc oxide coated with lignin comprises the following steps: S11. Add zinc nitrate hexahydrate to an ethanol aqueous solution, stir until dissolved, add urea, the molar ratio of zinc nitrate hexahydrate to urea is 1:1.5, stir and mix well, react at 190°C for 15h to obtain a precipitate, dry the precipitate and calcine at 500°C for 5h to obtain flaky nano zinc oxide; S12. The flaky nano zinc oxide prepared in step S11 is added to water and uniformly dispersed by ultrasonication to obtain a zinc oxide suspension; S13. Adding lignin to an alkaline aqueous solution and stirring until completely dissolved to obtain a lignin solution; S14. The lignin solution is added dropwise to the zinc oxide suspension and heated for reaction. The mass ratio of lignin to nano-sheet zinc oxide is 1:5. After the addition is completed, the pH value of the solution is adjusted to neutral, and the flaky zinc oxide coated with lignin is obtained by filtering. Example 2 The preparation method of the anti-yellowing polyurethane acrylate UV curing coating comprises the following steps: Weigh the following ingredients by weight: 70 parts of waterborne polyurethane acrylate, 10 parts of composite chopped fibers, 2.5 parts of phosphite, 2.5 parts of polydimethylsiloxane, 1.2 parts of dispersant BYK167, 3.5 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 4 parts of matte powder, 10 parts of dipropylene glycol methyl ether, and 130 parts of water; Add waterborne polyurethane acrylate into a container, and then add composite chopped fibers, phosphite, polydimethylsiloxane, dispersant BYK167, 2-hydroxy-2-methyl-1-phenyl-1-propanone, matte powder, dipropylene glycol methyl ether and water in sequence, and after each reaction raw material is added and stirred evenly, add the next raw material until all the raw materials are added and mixed and stirred evenly to obtain an anti-yellowing polyurethane acrylate UV curing coating; The method for preparing composite chopped fibers comprises the following steps: S1. After mixing the flaky zinc oxide coated with lignin and nano-calcium carbonate, the mass ratio of the flaky zinc oxide coated with lignin and calcium carbonate is 4:1, dispersed in a DMF solution, and a dispersant is added, and ultrasonic dispersion is performed for 60 minutes to obtain a mixed dispersion, and the concentration of calcium carbonate in DMF is 3wt%; S2. Dissolve polyacrylonitrile in DMF at a mass fraction of 15%, add the mixed dispersion at a volume ratio of 1:1, stir evenly and then vacuum degas to obtain a polyacrylonitrile skin spinning solution; S3. The ultraviolet light absorber is added to the DMF solution and dispersed uniformly by ultrasonication to obtain an ultraviolet light absorber solution; S4. The polyacrylonitrile was dissolved in DMF at a mass fraction of 15%, and a UV absorber solution was added, and the mixture was stirred evenly and vacuum degassed to obtain a polyacrylonitrile core spinning solution having a concentration of 7 wt %, wherein the content of the UV absorber in the polyacrylonitrile core spinning solution was 0.4 wt %; S5. Selecting circular and triangular cross-section spinnerets respectively, coaxially spinning the spinning solutions prepared in steps S2 and S4 to obtain circular cross-section fibers and triangular cross-section fibers; S6. The two fibers prepared in step S5 are immersed in a 0.1 mol / L hydrochloric acid solution to remove the nano-calcium carbonate in the cortex to obtain a porous surface fiber; S7. The porous fibers were chopped into 1-5 mm, respectively, and mixed according to a mass ratio, with the mass ratio of triangular cross-section fibers to circular cross-section fibers being 5:4 to obtain composite chopped fibers; The preparation method of the flaky zinc oxide coated with lignin comprises the following steps: S11. Add zinc nitrate hexahydrate to an ethanol aqueous solution, stir until dissolved, add urea, the molar ratio of zinc nitrate hexahydrate to urea is 1:2, stir and mix well, react at 180°C for 24h to obtain a precipitate, dry the precipitate and calcine at 550°C for 3h to obtain flaky nano zinc oxide; S12. The flaky nano zinc oxide prepared in step S11 is added to water and uniformly dispersed by ultrasonication to obtain a zinc oxide suspension; S13. Adding lignin to an alkaline aqueous solution and stirring until completely dissolved to obtain a lignin solution; S14. The lignin solution is added dropwise to the zinc oxide suspension and heated for reaction. The mass ratio of lignin to nano-sheet zinc oxide is 1:10. After the addition is completed, the pH value of the solution is adjusted to neutral, and the flaky zinc oxide coated with lignin is obtained by filtering. Example 3 The preparation method of the anti-yellowing polyurethane acrylate UV curing coating comprises the following steps: Weigh the following ingredients by weight: 62 parts of waterborne polyurethane acrylate, 6 parts of composite chopped fibers, 1.2 parts of phosphite, 1.5 parts of polydimethylsiloxane, 0.6 parts of dispersant BYK167, 2 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2.5 parts of matte powder, 6 parts of dipropylene glycol methyl ether, and 100 parts of water; Add waterborne polyurethane acrylate into a container, and then add composite chopped fibers, phosphite, polydimethylsiloxane, dispersant BYK167, 2-hydroxy-2-methyl-1-phenyl-1-propanone, matte powder, dipropylene glycol methyl ether and water in sequence, and after each reaction raw material is added and stirred evenly, add the next raw material until all the raw materials are added and mixed and stirred evenly to obtain an anti-yellowing polyurethane acrylate UV curing coating; The method for preparing composite chopped fibers comprises the following steps: S1. After mixing the flaky zinc oxide coated with lignin and nano-calcium carbonate, the mass ratio of the flaky zinc oxide coated with lignin and calcium carbonate is 2.5:1, dispersed in a DMF solution, and a dispersant is added, and ultrasonic dispersion is performed for 45 minutes to obtain a mixed dispersion, and the concentration of calcium carbonate in DMF is 1.5wt%; S2. Dissolve polyacrylonitrile in DMF at a mass fraction of 12%, add the mixed dispersion at a volume ratio of 1:1, stir evenly and then vacuum degas to obtain a polyacrylonitrile skin spinning solution; S3. The ultraviolet light absorber is added to the DMF solution and dispersed uniformly by ultrasonication to obtain an ultraviolet light absorber solution; S4. Dissolve polyacrylonitrile in DMF at a mass fraction of 12%, add a UV absorber solution, stir evenly and perform vacuum degassing to obtain a 5wt% polyacrylonitrile core spinning solution, wherein the content of the UV absorber in the polyacrylonitrile core spinning solution is 0.2wt%; S5. Selecting circular and triangular cross-section spinnerets respectively, coaxially spinning the spinning solutions prepared in steps S2 and S4 to obtain circular cross-section fibers and triangular cross-section fibers; S6. The two fibers prepared in step S5 are immersed in a 0.1 mol / L hydrochloric acid solution to remove the nano-calcium carbonate in the cortex to obtain a porous surface fiber; S7. The porous fibers were chopped into 1-5 mm and mixed in a mass ratio, with the mass ratio of triangular cross-section fibers to circular cross-section fibers being 10:4 to obtain composite chopped fibers; The preparation method of the flaky zinc oxide coated with lignin comprises the following steps: S11. Add zinc nitrate hexahydrate to an ethanol aqueous solution, stir until dissolved, add urea, the molar ratio of zinc nitrate hexahydrate to urea is 1:1.8, stir and mix well, react at 180°C for 20h to obtain a precipitate, dry the precipitate and calcine at 540°C for 4.5h to obtain flaky nano zinc oxide; S12. The flaky nano zinc oxide prepared in step S11 is added to water and uniformly dispersed by ultrasonication to obtain a zinc oxide suspension; S13. Adding lignin to an alkaline aqueous solution and stirring until completely dissolved to obtain a lignin solution; S14. The lignin solution is added dropwise to the zinc oxide suspension and heated for reaction. The mass ratio of lignin to nano-sheet zinc oxide is 1.2:10. After the addition is completed, the pH value of the solution is adjusted to neutral, and the flaky zinc oxide coated with lignin is obtained by filtering. Example 4 The preparation method of the anti-yellowing polyurethane acrylate UV curing coating comprises the following steps: Weigh the following ingredients by weight: 67 parts of waterborne polyurethane acrylate, 9 parts of composite chopped fibers, 2 parts of phosphite, 2 parts of polydimethylsiloxane, 1 part of dispersant BYK167, 3 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 3.5 parts of matte powder, 9 parts of dipropylene glycol methyl ether, and 120 parts of water; Add waterborne polyurethane acrylate into a container, and then add composite chopped fibers, phosphite, polydimethylsiloxane, dispersant BYK167, 2-hydroxy-2-methyl-1-phenyl-1-propanone, matte powder, dipropylene glycol methyl ether and water in sequence, and after each reaction raw material is added and stirred evenly, add the next raw material until all the raw materials are added and mixed and stirred evenly to obtain an anti-yellowing polyurethane acrylate UV curing coating; The method for preparing composite chopped fibers comprises the following steps: S1. After mixing the flaky zinc oxide coated with lignin and nano-calcium carbonate, the mass ratio of the flaky zinc oxide coated with lignin and calcium carbonate is 3.5:1, dispersed in a DMF solution, and a dispersant is added, and ultrasonic dispersion is performed for 45 minutes to obtain a mixed dispersion, and the concentration of calcium carbonate in DMF is 2.5wt%; S2. Dissolve polyacrylonitrile in DMF at a mass fraction of 14%, add the mixed dispersion at a volume ratio of 1:1, stir evenly and then vacuum degas to obtain a polyacrylonitrile skin spinning solution; S3. The ultraviolet light absorber is added to the DMF solution and dispersed uniformly by ultrasonication to obtain an ultraviolet light absorber solution; S4. The polyacrylonitrile was dissolved in DMF at a mass fraction of 14%, and a UV absorber solution was added, and the mixture was stirred evenly and vacuum degassed to obtain a polyacrylonitrile core spinning solution having a concentration of 7 wt %, wherein the content of the UV absorber in the polyacrylonitrile core spinning solution was 0.3 wt %; S5. Selecting circular and triangular cross-section spinnerets respectively, coaxially spinning the spinning solutions prepared in steps S2 and S4 to obtain circular cross-section fibers and triangular cross-section fibers; S6. The two fibers prepared in step S5 are immersed in a 0.1 mol / L hydrochloric acid solution to remove the nano-calcium carbonate in the cortex to obtain a porous surface fiber; S7. The porous fibers were chopped into 1-5 mm and mixed in a mass ratio of 10:6 to obtain composite chopped fibers; The preparation method of the flaky zinc oxide coated with lignin comprises the following steps: S11. Zinc nitrate hexahydrate was added to an ethanol aqueous solution, stirred until dissolved, and urea was added. The molar ratio of zinc nitrate hexahydrate to urea was 1:1.6. After stirring and mixing, the mixture was reacted at 190°C for 18h to obtain a precipitate. The precipitate was dried and calcined at 520°C for 3.5h to obtain flaky nano zinc oxide. S12. The flaky nano zinc oxide prepared in step S11 is added to water and uniformly dispersed by ultrasonication to obtain a zinc oxide suspension; S13. Adding lignin to an alkaline aqueous solution and stirring until completely dissolved to obtain a lignin solution; S14. The lignin solution is added dropwise to the zinc oxide suspension and heated for reaction. The mass ratio of lignin to nano-sheet zinc oxide is 1.8:10. After the addition is completed, the pH value of the solution is adjusted to neutral, and the flaky zinc oxide coated with lignin is obtained by filtering. Example 5 The preparation method of the anti-yellowing polyurethane acrylate UV curing coating comprises the following steps: Weigh the following ingredients by weight: 65 parts of waterborne polyurethane acrylate, 8 parts of composite chopped fibers, 1.6 parts of phosphite, 1.8 parts of polydimethylsiloxane, 0.8 parts of dispersant BYK167, 2.5 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 3 parts of matte powder, 8 parts of dipropylene glycol methyl ether, and 110 parts of water; Add waterborne polyurethane acrylate into a container, and then add composite chopped fibers, phosphite, polydimethylsiloxane, dispersant BYK167, 2-hydroxy-2-methyl-1-phenyl-1-propanone, matte powder, dipropylene glycol methyl ether and water in sequence, and after each reaction raw material is added and stirred evenly, add the next raw material until all the raw materials are added and mixed and stirred evenly to obtain an anti-yellowing polyurethane acrylate UV curing coating; The method for preparing composite chopped fibers comprises the following steps: S1. After mixing the flaky zinc oxide coated with lignin and nano-calcium carbonate, the mass ratio of the flaky zinc oxide coated with lignin and calcium carbonate is 3:1, dispersed in a DMF solution, and a dispersant is added, and ultrasonic dispersion is performed for 50 minutes to obtain a mixed dispersion, and the concentration of calcium carbonate in DMF is 2wt%; S2. Dissolve polyacrylonitrile in DMF at a mass fraction of 12%, add the mixed dispersion at a volume ratio of 1:1, stir evenly and then vacuum degas to obtain a polyacrylonitrile skin spinning solution; S3. The ultraviolet light absorber is added to the DMF solution and dispersed uniformly by ultrasonication to obtain an ultraviolet light absorber solution; S4. The polyacrylonitrile was dissolved in DMF at a mass fraction of 12%, and a UV absorber solution was added, and the mixture was stirred evenly and vacuum degassed to obtain a polyacrylonitrile core spinning solution having a concentration of 5 wt%, wherein the content of the UV absorber in the polyacrylonitrile core spinning solution was 0.25 wt%; S5. Selecting circular and triangular cross-section spinnerets respectively, coaxially spinning the spinning solutions prepared in steps S2 and S4 to obtain circular cross-section fibers and triangular cross-section fibers; S6. The two fibers prepared in step S5 are immersed in a 0.1 mol / L hydrochloric acid solution to remove the nano-calcium carbonate in the cortex to obtain a porous surface fiber; S7. The porous fibers were chopped into 1-5 mm, respectively, and mixed according to a mass ratio, with the mass ratio of triangular cross-section fibers to circular cross-section fibers being 2:1 to obtain composite chopped fibers; The preparation method of the flaky zinc oxide coated with lignin comprises the following steps: S11. Add zinc nitrate hexahydrate to an ethanol aqueous solution, stir until dissolved, add urea, the molar ratio of zinc nitrate hexahydrate to urea is 1:1.7, stir and mix well, react at 180°C for 20h to obtain a precipitate, dry the precipitate and calcine at 530°C for 4h to obtain flaky nano zinc oxide; S12. The flaky nano zinc oxide prepared in step S11 is added to water and uniformly dispersed by ultrasonication to obtain a zinc oxide suspension; S13. Adding lignin to an alkaline aqueous solution and stirring until completely dissolved to obtain a lignin solution; S14. The lignin solution is added dropwise to the zinc oxide suspension and heated for reaction. The mass ratio of lignin to nano-sheet zinc oxide is 1.5:10. After the addition is completed, the pH value of the solution is adjusted to neutral, and the flaky zinc oxide coated with lignin is obtained by filtering. Comparative Example 1 The difference between Comparative Example 1 and Example 5 is that in the composite chopped fibers, the mass ratio of the triangular cross-section fibers to the circular cross-section fibers is 1:1. Comparative Example 2 The difference between Comparative Example 2 and Example 5 is that only circular cross-section fibers are used. Comparative Example 3 The preparation method of the anti-yellowing polyurethane acrylate UV curing coating comprises the following steps: Weigh the following ingredients by weight: 65 parts of waterborne polyurethane acrylate, 8 parts of composite chopped fibers, 1.6 parts of phosphite, 1.8 parts of polydimethylsiloxane, 0.8 parts of dispersant BYK167, 2.5 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 3 parts of matte powder, 8 parts of dipropylene glycol methyl ether, and 110 parts of water; Add waterborne polyurethane acrylate into a container, and then add composite chopped fibers, phosphite, polydimethylsiloxane, dispersant BYK167, 2-hydroxy-2-methyl-1-phenyl-1-propanone, matte powder, dipropylene glycol methyl ether and water in sequence, and after each reaction raw material is added and stirred evenly, add the next raw material until all the raw materials are added and mixed and stirred evenly to obtain an anti-yellowing polyurethane acrylate UV curing coating; The method for preparing composite chopped fibers comprises the following steps: S1. The flaky zinc oxide coated with lignin is dispersed in a DMF solution, and a dispersant is added, and ultrasonic dispersion is performed for 50 min to obtain a dispersion, wherein the concentration of the flaky zinc oxide coated with lignin in DMF is 5 wt %; S2. Dissolve polyacrylonitrile in DMF at a mass fraction of 12%, add the mixed dispersion at a volume ratio of 1:1, stir evenly and then vacuum degas to obtain a polyacrylonitrile skin spinning solution; S3. The ultraviolet light absorber is added to the DMF solution and dispersed uniformly by ultrasonication to obtain an ultraviolet light absorber solution; S4. The polyacrylonitrile was dissolved in DMF at a mass fraction of 12%, and a UV absorber solution was added, and the mixture was stirred evenly and vacuum degassed to obtain a polyacrylonitrile core spinning solution having a concentration of 5 wt%, wherein the content of the UV absorber in the polyacrylonitrile core spinning solution was 0.25 wt%; S5. Selecting circular and triangular cross-section spinnerets respectively, coaxially spinning the spinning solutions prepared in steps S2 and S4 to obtain circular cross-section fibers and triangular cross-section fibers; S6. The above two fibers were chopped into 1-5 mm, respectively, and mixed according to the mass ratio, the mass ratio of the triangular cross-section fiber to the circular cross-section fiber was 2:1, and composite chopped fibers were obtained; The preparation method of the flaky zinc oxide coated with lignin comprises the following steps: S11. Add zinc nitrate hexahydrate to an ethanol aqueous solution, stir until dissolved, add urea, the molar ratio of zinc nitrate hexahydrate to urea is 1:1.7, stir and mix well, react at 180°C for 20h to obtain a precipitate, dry the precipitate and calcine at 530°C for 4h to obtain flaky nano zinc oxide; S12. The flaky nano zinc oxide prepared in step S11 is added to water and uniformly dispersed by ultrasonication to obtain a zinc oxide suspension; S13. Adding lignin to an alkaline aqueous solution and stirring until completely dissolved to obtain a lignin solution; S14. The lignin solution is added dropwise to the zinc oxide suspension and heated for reaction. The mass ratio of lignin to nano-sheet zinc oxide is 1.5:10. After the addition is completed, the pH value of the solution is adjusted to neutral, and the flaky zinc oxide coated with lignin is obtained by filtering. Comparative Example 4 The preparation method of the anti-yellowing polyurethane acrylate UV curing coating comprises the following steps: Weigh the following ingredients by weight: 65 parts of waterborne polyurethane acrylate, 8 parts of composite chopped fibers, 1.6 parts of phosphite, 1.8 parts of polydimethylsiloxane, 0.8 parts of dispersant BYK167, 2.5 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 3 parts of matte powder, 8 parts of dipropylene glycol methyl ether, and 110 parts of water; Add waterborne polyurethane acrylate into a container, and then add composite chopped fibers, phosphite, polydimethylsiloxane, dispersant BYK167, 2-hydroxy-2-methyl-1-phenyl-1-propanone, matte powder, dipropylene glycol methyl ether and water in sequence, and after each reaction raw material is added and stirred evenly, add the next raw material until all the raw materials are added and mixed and stirred evenly to obtain an anti-yellowing polyurethane acrylate UV curing coating; The method for preparing composite chopped fibers comprises the following steps: S1. After mixing the flaky zinc oxide coated with lignin and nano-calcium carbonate, the mass ratio of the flaky zinc oxide coated with lignin and calcium carbonate is 3:1, dispersed in a DMF solution, and a dispersant is added, and ultrasonic dispersion is performed for 45 minutes to obtain a mixed dispersion, and the concentration of calcium carbonate in DMF is 2wt%; S2. Dissolve polyacrylonitrile in DMF at a mass fraction of 12%, add the mixed dispersion at a volume ratio of 1:1, stir evenly and then vacuum degas to obtain a polyacrylonitrile spinning solution; S3. Selecting circular and triangular cross-section spinnerets respectively, and coaxially spinning the spinning solution prepared in step S2 to obtain circular cross-section fibers and triangular cross-section fibers; S4. The two fibers prepared in step S3 were immersed in a 0.1 mol / L hydrochloric acid solution to remove the nano-calcium carbonate to obtain a porous surface fiber; S5. The porous fibers were chopped into 1-5 mm and mixed in a mass ratio of 2:1 to obtain composite chopped fibers; The preparation method of the flaky zinc oxide coated with lignin comprises the following steps: S11. Add zinc nitrate hexahydrate to an ethanol aqueous solution, stir until dissolved, add urea, the molar ratio of zinc nitrate hexahydrate to urea is 1:1.7, stir and mix well, react at 180°C for 20h to obtain a precipitate, dry the precipitate and calcine at 530°C for 4h to obtain flaky nano zinc oxide; S12. The flaky nano zinc oxide prepared in step S11 is added to water and uniformly dispersed by ultrasonication to obtain a zinc oxide suspension; S13. Adding lignin to an alkaline aqueous solution and stirring until completely dissolved to obtain a lignin solution; S14. The lignin solution is added dropwise to the zinc oxide suspension and heated for reaction. The mass ratio of lignin to nano-sheet zinc oxide is 1.5:10. After the addition is completed, the pH value of the solution is adjusted to neutral, and the flaky zinc oxide coated with lignin is obtained by filtering. Comparative Example 5 The preparation method of the anti-yellowing polyurethane acrylate UV curing coating comprises the following steps: Weigh the following ingredients by weight: 65 parts of waterborne polyurethane acrylate, 8 parts of composite chopped fibers, 1.6 parts of phosphite, 1.8 parts of polydimethylsiloxane, 0.8 parts of dispersant BYK167, 2.5 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 3 parts of matte powder, 8 parts of dipropylene glycol methyl ether, and 110 parts of water; Add waterborne polyurethane acrylate into a container, and then add composite chopped fibers, phosphite, polydimethylsiloxane, dispersant BYK167, 2-hydroxy-2-methyl-1-phenyl-1-propanone, matte powder, dipropylene glycol methyl ether and water in sequence, and after each reaction raw material is added and stirred evenly, add the next raw material until all the raw materials are added and mixed and stirred evenly to obtain an anti-yellowing polyurethane acrylate UV curing coating; The method for preparing composite chopped fibers comprises the following steps: S1. After mixing the flaky zinc oxide and nano-calcium carbonate, the mass ratio of the flaky zinc oxide and calcium carbonate is 3:1, dispersed in a DMF solution, and a dispersant is added, and ultrasonic dispersion is performed for 40 minutes to obtain a mixed dispersion, and the concentration of calcium carbonate in DMF is 2wt%; S2. Dissolve polyacrylonitrile in DMF at a mass fraction of 12%, add the mixed dispersion at a volume ratio of 1:1, stir evenly and then vacuum degas to obtain a polyacrylonitrile skin spinning solution; S3. The ultraviolet light absorber is added to the DMF solution and dispersed uniformly by ultrasonication to obtain an ultraviolet light absorber solution; S4. The polyacrylonitrile was dissolved in DMF at a mass fraction of 12%, and a UV absorber solution was added, and the mixture was stirred evenly and vacuum degassed to obtain a polyacrylonitrile core spinning solution having a concentration of 5 wt%, wherein the content of the UV absorber in the polyacrylonitrile core spinning solution was 0.25 wt%; S5. Selecting circular and triangular cross-section spinnerets respectively, coaxially spinning the spinning solutions prepared in steps S2 and S4 to obtain circular cross-section fibers and triangular cross-section fibers; S6. The two fibers prepared in step S5 are immersed in a 0.1 mol / L hydrochloric acid solution to remove the nano-calcium carbonate in the cortex to obtain a porous surface fiber; S7. The fibers with porous surfaces are chopped into 1-5 mm, respectively, and mixed according to a mass ratio, wherein the mass ratio of the triangular cross-section fibers to the circular cross-section fibers is 2:1, to obtain composite chopped fibers. Comparative Example 6 The preparation method of the anti-yellowing polyurethane acrylate UV curing coating comprises the following steps: Weigh the following ingredients by weight: 65 parts of waterborne polyurethane acrylate, 8 parts of composite chopped fibers, 1.6 parts of phosphite, 1.8 parts of polydimethylsiloxane, 0.8 parts of dispersant BYK167, 2.5 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 3 parts of matte powder, 8 parts of dipropylene glycol methyl ether, and 110 parts of water; Add waterborne polyurethane acrylate into a container, and then add composite chopped fibers, phosphite, polydimethylsiloxane, dispersant BYK167, 2-hydroxy-2-methyl-1-phenyl-1-propanone, matte powder, dipropylene glycol methyl ether and water in sequence, and after each reaction raw material is added and stirred evenly, add the next raw material until all the raw materials are added and mixed and stirred evenly to obtain an anti-yellowing polyurethane acrylate UV curing coating; The method for preparing composite chopped fibers comprises the following steps: S1. The flaky zinc oxide coated with lignin was dispersed in a DMF solution, and a dispersant was added, and ultrasonic dispersion was performed for 45 min to obtain a dispersion having a concentration of 4 wt%; S2. Dissolve polyacrylonitrile in DMF at a mass fraction of 14%, add the mixed dispersion at a volume ratio of 1:1, stir evenly and then vacuum degas to obtain a polyacrylonitrile core spinning solution; S3. The ultraviolet light absorber is added to the DMF solution and dispersed uniformly by ultrasonication to obtain an ultraviolet light absorber solution; S4. The polyacrylonitrile was dissolved in DMF at a mass fraction of 12%, and a UV absorber solution was added, and the mixture was stirred evenly and vacuum degassed to obtain a 6wt% polyacrylonitrile cortex spinning solution, wherein the content of the UV absorber in the polyacrylonitrile cortex spinning solution was 0.25wt%; S5. Selecting circular and triangular cross-section spinnerets respectively, coaxially spinning the spinning solutions prepared in steps S2 and S4 to obtain circular cross-section fibers and triangular cross-section fibers; S6. The above two fibers were chopped into 1-5 mm, respectively, and mixed according to the mass ratio, the mass ratio of the triangular cross-section fiber to the circular cross-section fiber was 2:1, and composite chopped fibers were obtained; The preparation method of the flaky zinc oxide coated with lignin comprises the following steps: S11. Add zinc nitrate hexahydrate to an ethanol aqueous solution, stir until dissolved, add urea, the molar ratio of zinc nitrate hexahydrate to urea is 1:1.7, stir and mix well, react at 180°C for 20h to obtain a precipitate, dry the precipitate and calcine at 530°C for 4h to obtain flaky nano zinc oxide; S12. The flaky nano zinc oxide prepared in step S11 is added to water and uniformly dispersed by ultrasonication to obtain a zinc oxide suspension; S13. Adding lignin to an alkaline aqueous solution and stirring until completely dissolved to obtain a lignin solution; S14. The lignin solution is added dropwise to the zinc oxide suspension and heated for reaction. The mass ratio of lignin to nano-sheet zinc oxide is 1.5:10. After the addition is completed, the pH value of the solution is adjusted to neutral, and the flaky zinc oxide coated with lignin is obtained by filtering. Comparative Example 7 The difference between Comparative Example 7 and Example 5 is that the content of composite chopped fibers in the coating is different, and the components are weighed according to the following weight parts: 65 parts of water-based polyurethane acrylate, 3 parts of composite chopped fibers, 1.6 parts of phosphite, 1.8 parts of polydimethylsiloxane, 0.8 parts of dispersant BYK167, 2.5 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 3 parts of matte powder, 8 parts of dipropylene glycol methyl ether, and 110 parts of water. Comparative Example 8 The difference between Comparative Example 1 and Example 5 is that the length of the composite chopped fibers is 5-8 mm. The UV-curable coating prepared in the above examples and comparative examples is applied to the substrate in an amount of 8-20 g / m 2 , the number of coating passes is unlimited; finally, the coating composition is cured by ultraviolet irradiation, and the adhesion is tested respectively. The test properties such as yellowing after 1000 hours of ultraviolet irradiation are shown in Table 1 below, wherein, coating adhesion: measured according to ASTM D3359-09; yellowing test: measured according to GB / T 23983-2009; flexibility test: tested according to GB / T 1731-2020. Adhesion Yellowing after 1000h UV exposure / ΔE Flexibility / mm Example 1 5B 0.89 0.5 Example 2 5B 0.85 1 Example 3 5B 0.92 1 Example 4 5B 0.88 0.5 Example 5 5B 0.82 0.5 Comparative Example 1 5B 1.23 1 Comparative Example 2 5B 3.69 1 Comparative Example 3 5B 4.56 1.5 Comparative Example 4 5B 2.89 0.5 Comparative Example 5 5B 1.44 1 Comparative Example 6 5B 2.16 0.5 Comparative Example 7 3B 2.54 1.5 Comparative Example 8 3B 0.91 1.5 Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. An anti-yellowing polyurethane acrylate UV curing coating, characterized in that: Contains the following components by weight: 60-70 parts of waterborne polyurethane acrylate, 5-10 parts of composite chopped fibers, 0.8-2.5 parts of antioxidant, 0.8-2.5 parts of leveling agent, 0.4-1.2 parts of dispersant, 1.5-3.5 parts of UV photoinitiator, 2-4 parts of matte powder, 5-10 parts of film-forming aid, 90-130 parts of water; Wherein, the antioxidant is any one or more of phosphite, antioxidant 1010 or antioxidant 168; The leveling agent is any one or more of polydimethylsiloxane, polydimethylphenylsiloxane or polyether modified polydimethylsiloxane; The dispersant is any one or more of dispersant BYK190, dispersant BYK167, dispersant BYK2050 or dispersant BYK-W966; The film-forming aid is a medium film-forming aid including any one or more of dipropylene glycol methyl ether, dipropylene glycol butyl ether, alcohol ester dodecahydrate, and diethylene glycol butyl ether; The photoinitiator is any one or more of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

2. The anti-yellowing polyurethane acrylate UV curing coating according to claim 1, characterized in that: The composite chopped fibers are a mixture of triangular cross-section fibers and circular cross-section fibers, the lengths of the triangular cross-section fibers and the circular cross-section fibers are 1-5 mm, and the mass ratio of the triangular cross-section fibers to the circular cross-section fibers is 10:3-8.

3. The anti-yellowing polyurethane acrylate UV curing coating according to claim 1, characterized in that: The method for preparing the composite chopped fibers comprises the following steps: S1. The flaky zinc oxide coated with lignin and nano-calcium carbonate were mixed and dispersed in a DMF solution, and a dispersant was added and ultrasonically dispersed for 30-60 min to obtain a mixed dispersion; S2. Dissolve polyacrylonitrile in DMF at a mass fraction of 10-15%, add the mixed dispersion at a volume ratio of 1:1, stir evenly and then vacuum degas to obtain a polyacrylonitrile cortex spinning solution; S3. The ultraviolet light absorber is added to the DMF solution and dispersed uniformly by ultrasonication to obtain an ultraviolet light absorber solution; S4. Dissolve polyacrylonitrile in DMF at a mass fraction of 10-15%, add a UV absorber solution, stir evenly, and then vacuum degas to obtain a polyacrylonitrile core spinning solution; S5. Selecting circular and triangular cross-section spinnerets respectively, coaxially spinning the spinning solutions prepared in steps S2 and S4 to obtain circular cross-section fibers and triangular cross-section fibers; S6. The two fibers prepared in step S5 are immersed in an inorganic acid solution to remove the nano-calcium carbonate in the cortex to obtain a porous surface fiber; S7. The fibers with porous surfaces are chopped into short pieces respectively, and the mixture is mixed according to a mass ratio to obtain composite chopped fibers.

4. The anti-yellowing polyurethane acrylate UV curing coating according to claim 3, characterized in that: The preparation method of the flaky zinc oxide coated with lignin comprises the following steps: S11. Add zinc nitrate hexahydrate to an ethanol aqueous solution, stir until dissolved, add urea, the molar ratio of zinc nitrate hexahydrate to urea is 1:1.5-2, stir and mix well, react at 180-190°C for 15-24h to obtain a precipitate, dry the precipitate and calcine at 500-550°C for 3-5h to obtain flaky nano zinc oxide; S12. The flaky nano zinc oxide prepared in step S11 is added to water and uniformly dispersed by ultrasonication to obtain a zinc oxide suspension; S13. Adding lignin to an alkaline aqueous solution and stirring until completely dissolved to obtain a lignin solution; S14. Add the lignin solution dropwise to the zinc oxide suspension and heat to react. The mass ratio of lignin to nano-flaky zinc oxide is 1-2:

10. After the addition is complete, adjust the pH value of the solution to neutral and filter to obtain flaky zinc oxide coated with lignin.

5. The anti-yellowing polyurethane acrylate UV curing coating according to claim 3, characterized in that: In the step S1, the mass ratio of the flaky zinc oxide coated with lignin to calcium carbonate is 2-4:1, and the concentration of calcium carbonate in DMF is 1-3 wt%.

6. The anti-yellowing polyurethane acrylate UV curing coating according to claim 3, characterized in that: In the step S4, the content of the ultraviolet light absorber in the polyacrylonitrile core layer spinning solution is 0.1-0.4 wt %.

7. The anti-yellowing polyurethane acrylate UV curing coating according to claim 3, characterized in that: The inorganic acid in step S6 is any one of nitric acid, hydrochloric acid or sulfuric acid.

8. The method for preparing the anti-yellowing polyurethane acrylate UV curing coating according to claims 1-7, characterized in that: The following steps are involved: First, the water-based polyurethane acrylate is added into a container, and then composite chopped fibers, antioxidants, leveling agents, dispersants, UV photoinitiators, matte powders, film-forming aids and water are added in sequence. Each time a reaction raw material is added, it is stirred evenly before adding the next raw material until all the raw materials are added and mixed and stirred evenly to obtain an anti-yellowing polyurethane acrylate UV curing coating.

Citation Information

Patent Citations

  • Lignin carbon / zinc oxide nano composite material as well as preparation and application thereof

    CN117160435A

  • Composite reinforced resin composition

    JP1996085761A